Hilah dalam Produk Pembiayaan Syariah: (Evaluasi Skema Akad KPR Murabahah dan Gadai Syariah) - Izzatul Mardhiah (Universitas Negeri Jakarta, 2017)
This article aims to evaluate the financing products of Islamic Financial Institutions that are suspected to contain hilah (legal stratagem). This research uses library study with qualitative design through fiqh and Islamic finance approach. Based on some indicators and parameters of hilah, it is found that Murabahah scheme in Islamic mortgages and al-Rahn and al-Ijarah scheme in Islamic pawn contract were formulated by hilah methods, only Islamic mortgages can be categorized into permissible hilah, while the Islamic pawn included into impermissible one. Thus it can be determined also that Murabahah mortgage can be used for a limited period, and should be reformulated after the loss of a variety of technical barriers, otherwise Islamic Pawn product should be immediatedly reformulated in line with the provisions of law and does not resemble the interest based of conventional mortgage.